Kawasaki Disease, MIS-C and COVID-19 - Ying-Hsien Huang; Ho-Chang Kuo (MDPI AG, 2023)
Kawasaki disease (KD) is a form of systemic vasculitis characterized by inflammation of blood vessels throughout the body, and its exact cause remains unknown [...]